Cumulative Exposure to Ideal Cardiovascular Health and Incident Diabetes in a Chinese Population: The Kailuan Study - Liu, X.; Cui, L.; Wang, A.; Wang, X.; Song, Q.; Li, S.; Shi, J.; Zhao, X.; Chen, S.; Du, X.; Ji, C.; Huxley, Rachel; et al. (Wiley-Blackwell, 2016)
Background: It is unclear whether ideal cardiovascular health (CVH), and particularly cumulative exposure to ideal CVH (cumCVH), is associated with incident diabetes. We aimed to fill this research gap. Methods and Results: The Kailuan Study is a prospective cohort of 101 510 adults aged 18 to 98 years recruited in 2006-2007 and who were subsequently followed up at 2- (Exam 2), 4- (Exam 3), and 6 (Exam 4)-year intervals after baseline. The main analysis is restricted to those individuals with complete follow-up at all 4 examinations and who had no history of diabetes until Exam 3. Cumulative exposure to ideal CVH (cumCVH) was calculated as the summed CVH score for each examination multiplied by the time between the 2 examinations (score×year). Logistic regression models were used to assess the association between cumCVH and incident diabetes. In fully adjusted models, compared with the lowest quintile of cumCVH, individuals in the highest quintile had ~68% (95% confidence interval [CI] 60-75) lower risk for incident diabetes (compared with 61% [95% CI 52-69] lower risk when using baseline CVH). Every additional year lived with a 1-unit increase in ideal CVH was associated with a 24% (95% CI 21-28) reduction in incident diabetes. Conclusions: Ideal CVH is associated with a reduced incidence of diabetes, but the association is likely to be underestimated if baseline measures of CVH exposure are used. Measures of cumulative exposure to ideal CVH are more likely to reflect lifetime risk of diabetes and possibly other health outcomes. CLINICAL TRIAL REGISTRATION: URL: https://www.chictr.org. Unique identifier: ChiCTRTNC-11001489.